Could Melissa Officinalis Extract Restore Streptozotocin-Induced Spatial Memory Impairment in Rats? - Fatemeh Sabbaghziarani; Sharareh Rasapour; Keywan Mortezaee; Shahrbano Oryan; Mohammad Sharifzadeh; Mahnaz Khanavi; Gholamreza Hassanzadeh (Negah Institute for Scientific Communication, 2014)
Introduction: Alzheimer disease is a progressive and irreversible neuropsychiatric disorder. Melissa Officinalis improves anxiety and clinical dementia symptoms caused by AD therefore, the purpose of the present study was to evaluate the effect of Mellisa extract on spatial memory deficit induced by STZ in MWM examination of male wistar rats. Methods: In the present study, 112 male wistar rats (220-270g) were used. Spatial learning deficit was induced by bilateral ICV injection of STZ (3mg/kg) via cannula then, the Melissa extract in different doses administrated by gavage and Morris Water Maze for measurement of spatial learning parameters was performed. Results: The results of this study demonstrated that gavage of the 200mg/kg of Melissa officinalis in combination with STZ, followed by significant reduction in two parameters: Time and Distance. Conclusion: Totally, the data indicate possible therapeutic value of M. officinalis extract on spatial learning improvement.